Storing vector-vortex states of light in an intra-atomic frequency-comb quantum memory. - Chanchal; G, P. Teja; K. Goyal, Sandeep (American Physical Society, 2021)
Photons are a prominent candidate for long-distance quantum communication and quantum information processing. Certain quantum information processing tasks require storage and faithful retrieval of single photons, preserving the internal states of the photons. Here we propose a method to store orbital angular momentum and polarization states of light which facilitates the storage of the vector-vortex states in the intra-atomic frequency-comb-based quantum memory. We show that an atomic ensemble with two intra-atomic frequency combs corresponding to Δ m = ± 1 transitions of similar frequency is sufficient for a robust and efficient quantum memory for vector-vortex states of light. As an example, we show that Cs and Rb atoms are good candidates for storing these internal modes of light.
Only IISER Mohali authors are available in the record
Keywords: Polarization of light; Quantum memories; Quantum description of light-matter interaction